(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the fulfillment of the established criteria for the judicial assistance of insulin analogs for patients with Diabetes mellitus at the Centro de Especialidades Médico Odontológica (CEMO), in Belém, Pará. Method: This is a case study, carried out between August 2018 and June 2019, using convenience sampling, with inclusion criteria, users with Diabetes mellitus in the age group between 50 and 59 years old, of both sexes, using insulin analogous lispro (Humalog® ), aspart (NovoRapid®), glulisine (Lispro®), glargine (Lantus®), detemir (Levemir®), degludeca (Tresiba®), on demand. Results: Compliance with the inclusion criteria was evidenced; however, not the criteria for the maintenance and exclusion of the program for access to similar insulins under judicial demand. Conclusion: It appears that the criteria established for the judicial assistance of insulin analogues for users with Diabetes mellitus at the Centro de Especialidades Médico Odontológica (CEMO) in the city of Belém, Pará, are partially fulfilled.